Developmental regulation of pectic polysaccharides in the root meristem of Arabidopsis - Dolan, L; Linstead, P; Roberts, K (1997)
JIM 5, an antibody that recognizes a relatively unesterified pectic epitope, distinguishes between dividing (meristematic) and non-dividing (central cells of the quiescent centre) cells in the Arabidopsis root tip, indicating that non-dividing cell walls contain higher levels of relatively unesterified pectin than dividing cells. JIM 7, an antibody that recognizes a relatively methyl esterified epitope, labels all cell walls uniformly throughout the root, suggesting that there is little variation in the relatively methyl esterified pectic component in the two cell types. These observations suggest that the characteristics of cell walls in the root tip result in part from modulations in the amount of unesterified and non-methyl esterified pectin.